Willingness to Pay Towards Healthier Bakery Product: Application of Health Belief Model - Syahputri, Nabila; Aprianingsih, Atik (Journal of Business and Management, 2015)
Abstract. Food consumption patterns are rapidly changing nowadays as a result of environmental issues, nutritional value concern of food, and health issues. As the interest of healthy lifestyle in Indonesia is on the rising, it is still unknown the specific customer reference in a particular food. The researcher put interest in the further investigation about a healthier alternative on bakery foods. This research aimed to assess the willingness to pay towards healthier bakery product using Health Belief Model as the research framework. The research was using eight main construct of Health Belief Model, which is Perceived Barriers(PB), Perceived Susceptibility(PS), Perceived Severity(PSE), Perceived Benefit(PBE), Self Efficacy(SE), Cues to Action(CA), General Health Orientation(GHO), Willingness to Use (WTU) and also Willingness to Pay(WTP) as the extension as the model to construct an 45-item questionnaire to assess respondentâ€™s willingness to pay towards healthier bakery product in Bandung in particular. Using non-probability sampling method, the questionnaire was spread to 150 respondents in Bandung with age 18-34. After the responses screened and proved valid and reliable, it was analyzed using Path Analysis to investigate the relationship between variable. The results of this research reveal that the there are three variables which is Perceived Severity, Perceived Benefit and General Health Orientation that make significant relation to Willingness to Use as well as Willingness to Use also make significant relation to Willingness to Pay. Not all of the hypotheses in this research are supported by the result. However, the result related to the previous study by Masoud et al. (2014). The implications of this research from both practical and theoretical aspect are discussed for the entrepreneurial suggestion as well as for future research. Â Keywords: Willingness to Pay, Health Belief Model, HealthÂ